State's Protective Measure towards Criminalization of Investigative Journalists - Zenny Rezania Dewantary; Gratianus Prikasetya (IJCLS (Indonesian Journal of Criminal Law Studies), 2020)
Investigative journalism is a form of news covering activities where the journalists are investigating deeply the information and/or events. Investigative journalism utilizes investigation technique because general methods of journalistic would not suffice, due to the nature of objects being investigated. To that extent, the journalists often face threats and dangers that arise the importance of protective measure by Indonesian State authorities. Using normative-empirical legal research method, this research was conducted to describe the design of legal protection towards investigative journalists. The protective measure towards investigative journalists substantially covered by Journalistic Ethical Code and The Press Law; Registered press company, particularly press company founded as legal entity; Strong role of Press Council in advocating investigative journalists; Article 50 of Indonesian Penal Code as legitimacy of freedom of press; MoUs between Press Council and law enforcers. The implementation in the field requires investigative journalists to uphold carefullness due to the culture of law enforcement in particular and society in general that is still putting criminal law as primum remedium towards press.